2018
DOI: 10.1016/j.agee.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the landscape-dependent restoration potential of abandoned farmland using a hierarchical model of bird communities

Abstract: Expansion and intensification of agriculture have led to an immense decrease in biodiversity. However, the area of abandoned farmland has been increasing globally in recent years and is expected to provide novel habitats for various organisms. Despite the promising potential for biodiversity conservation in agricultural landscapes, few studies have compared biodiversity among multiple land use types, including abandoned farmland. We examined the effects of major land use types (wetland, grassland, forest, farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…It may be difficult to restore forest ecosystems to a composition resembling that of natural forests if there are no seed sources in the surrounding areas [82,83]. However, open-land vegetation (e.g., grassland and wetland) can be restored due to the high seed dispersal ability of grass species [84][85][86][87][88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be difficult to restore forest ecosystems to a composition resembling that of natural forests if there are no seed sources in the surrounding areas [82,83]. However, open-land vegetation (e.g., grassland and wetland) can be restored due to the high seed dispersal ability of grass species [84][85][86][87][88].…”
Section: Discussionmentioning
confidence: 99%
“…On Sado island, abandoned paddies function as foraging habitats of the reintroduced Crested Ibis, Nipponia nippon [89], and in the Lake Inbanuma watershed, abandoned paddies on small valley bottoms have potential for multipurpose usages such as flood control, water purification, and wetland biodiversity [90]. In Hokkaido, the abandoned farmlands could be used to harbor organisms of wetland ecosystems [84][85][86][87] and provide wetland green infrastructure [91]. Natural recovery of vegetation in abandoned farmlands will proceed in the future, although the government would prefer to maintain the present farmlands through subsidies and land management policies.…”
Section: Discussionmentioning
confidence: 99%
“…A single surveyor walked slowly (1 km h −1 ) on the survey route between sunrise and 08.00 and counted abundance of seen or heard individuals within 40 m width from the survey route. We assumed that this sampling range (less than 40 m from the observer) ensured high detection probabilities of birds across forests and grassland sites [39][40][41]. Flying individuals were not recorded.…”
Section: (D) Field Samplingmentioning
confidence: 99%
“…So, recent researches shown that ecosystem de‐domestication may benefit for several taxa, such as birds (Hanioka et al. ), ground beetles (Yamanaka et al. ), moths (Miranda et al.…”
Section: Discussionmentioning
confidence: 99%